Romanticism, medicine, and the poet's body - Allard, James Robert (Ashgate, 2007)
Body conscious: vitalities, corporealities, and the anatomies of romantic medicine – Flesh and blood: Wordsworth, Baillie, and the romantic body – Great vital organs: Thelwall's The peripatetic, radical materialism, and the body politic – Shap'd and palpable: Keats and the poet's body – The body's laws: flesh, souls, and transgression in Beddoes's Death's jest-book – Apollo's poets
Includes bibliographical references
Keywords: Keats; John; Thelwall; John; Beddoes; Thomas Lovell; English literature; Medicine in literature; Literature and medicine; Physicians as authors; Romanticism